The state of primary health care in south Asia - Prinja, Shankar; Purohit, Neha; Kaur, Navneet; Rajapaksa, Lalini; Sarker, Malabika; Zaidi, Raza; Bennett, Sara; Rao, Krishna (The lancet. Global health, 2024)
The south Asian region (SAR) is home to 1·74 billion people, corresponding to 22% of the global population. The region faces several challenges pertaining to changing epidemiology, rapid urbanisation, and social and economic concerns, which affect health outcomes. Primary health care (PHC) is a cost-effective strategy to respond to these challenges through integrated service delivery, multi-sectoral action, and empowered communities. The PHC approach has historically been an important cornerstone of health policy in SAR countries. However, the region is yet to fully reap the benefits of PHC-oriented health systems. Our introductory paper in this Lancet Series on PHC in the SAR describes the existing PHC delivery structure in five SAR nations (ie, Bangladesh, India, Nepal, Pakistan, and Sri Lanka) and critically appraises PHC performance to identify its enablers and barriers. The paper proposes investing in a shared culture of innovation and collaboration for revitalisation of PHC in the region.